Transhumant sheep and goat farming and the use of rangelands in Greece - Karatassiou M.; Galidaki G.; Ragkos A.; Stefopoulos K.; Sklavou P.; Parissi Z.M.; Lagka V. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The transhumant sheep and goat farming system has a dynamic and multidimensional character which is manifested through its social, economic and environmental impact. Concerning its environmental role, the system contributes substantially to safeguarding biodiversity, as well as to the formulation of the structure of grazed rangelands, influenced by the different nutritional habits of the animals. The purpose of this paper is to provide an overview of rangelands used by small transhumant ruminants in Greece, alongside with the main structural characteristics of the system. For each Greek region the areas grazed by transhumant flocks are presented along side with the area grazed by non-transhumant sheep and goats, categorized by altitude. The results demonstrate the importance of transhumance in the management of pseudoalpine rangelands, but also in the lowlands. The design of an integrated land use strategy is essential for the Greek livestock sector, especially under the light of the new Common Agricultural policy, and transhumance should be an integral part in designing effective rangeland management schemes.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)